2009
DOI: 10.1039/b810979f
|View full text |Cite
|
Sign up to set email alerts
|

SAC1 lipid phosphatase and growth control of the secretory pathway

Abstract: Phosphoinositide lipids play a dual role in cell physiology. Specific sets of these molecules are short-lived downstream mediators of growth signals, regulating cell survival and differentiation. In addition, distinct classes of phosphoinositide lipids function as constitutive mediators of membrane traffic and organelle identity. Recent work has provided the first direct evidence that phosphoinositides also play a direct role in linking protein secretion with cell growth and proliferation. This review focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 96 publications
(139 reference statements)
0
39
0
Order By: Relevance
“…Indeed, Sac3 belongs to the group of relatively non-specific evolutionarily conserved Sac1 homology-containing inositol polyphosphate phosphatases (Fig. 7.2) able to hydrolyze phosphate from any of the D-3, -4 or -5 positions in inositol in in vitro assays (Hughes et al 2000;Blagoveshchenskaya and Mayinger 2009;Majerus and York 2009). Although recombinant Fig4, the yeast Sac3 ortholog, hydrolyzes exclusively the D-5 phosphate in PtdIns(3,5)P 2 (Rudge et al 2004), such specificity is not reproduced with human and rat Sac3 proteins Yuan et al 2007).…”
Section: Arpikfyve and Sac3: The Pas Regulatory Triomentioning
confidence: 99%
“…Indeed, Sac3 belongs to the group of relatively non-specific evolutionarily conserved Sac1 homology-containing inositol polyphosphate phosphatases (Fig. 7.2) able to hydrolyze phosphate from any of the D-3, -4 or -5 positions in inositol in in vitro assays (Hughes et al 2000;Blagoveshchenskaya and Mayinger 2009;Majerus and York 2009). Although recombinant Fig4, the yeast Sac3 ortholog, hydrolyzes exclusively the D-5 phosphate in PtdIns(3,5)P 2 (Rudge et al 2004), such specificity is not reproduced with human and rat Sac3 proteins Yuan et al 2007).…”
Section: Arpikfyve and Sac3: The Pas Regulatory Triomentioning
confidence: 99%
“…In S. cerevisiae, Sac1 is required for a variety of cell processes, including organization of actin cytoskeleton, secretory traffic, lipid metabolism and ER ATP transport (Blagoveshchenskaya and Mayinger, 2009;Foti et al, 2001). In this study, we identified homologous Sac1 in the dimorphic fungus, C. albicans, and characterized its functions in morphogenesis, cell wall integrity (CWI) and pathogenicity.…”
Section: Discussionmentioning
confidence: 98%
“…Further studies demonstrated that this protein participates in many cellular processes, such as organization of the actin cytoskeleton, secretory pathway, vacuolar function, ER function and sphingolipid metabolism (Blagoveshchenskaya and Mayinger, 2009;Foti et al, 2001). Deletion of ScSAC1 also results in inositol auxotrophy (Whitters et al, 1993), implying an essential role in inositol metabolism.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported previously that SAC1 is localized to the Golgi membranes only when cells are starved for nutrients or growth factors, but remains in the ER under normal growth conditions (23,24). Given the role for PI(4)P in vesicle traffic from the trans Golgi network, starvation conditions that lodge SAC1 and thus deplete the local supply of PI(4)P in the Golgi may suppress anterograde traffic in cells that must cease net cell growth.…”
Section: Significancementioning
confidence: 95%